2020
DOI: 10.1093/gastro/goaa018
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus type 2 drives metabolic reprogramming to promote pancreatic cancer growth

Abstract: Background Diabetes mellitus type 2 (DM2) is a modifiable risk factor associated with pancreatic carcinogenesis and tumor progression on the basis of epidemiology studies, but the biological mechanisms are not completely understood. The purpose of this study is to demonstrate direct evidence for the mechanisms mediating these epidemiologic phenomena. Our hypothesis is that DM2 accelerates pancreatic cancer growth and that metformin treatment has a beneficial impact. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Experimental evidence is emerging to explain the molecular mechanism linking T2DM and PDAC. They include the roles of cellular senescence promoted by both T2DM and obesity[ 43 ], advanced glycation end products and its receptor[ 44 ], metabolic reprogramming by hyperglycaemia[ 45 ] and the interplay between non-alcoholic fatty pancreas development in the milieu of obesity and diabetes[ 46 ].…”
Section: Mechanism Of Development Of Pc In Long-standing T2dmmentioning
confidence: 99%
“…Experimental evidence is emerging to explain the molecular mechanism linking T2DM and PDAC. They include the roles of cellular senescence promoted by both T2DM and obesity[ 43 ], advanced glycation end products and its receptor[ 44 ], metabolic reprogramming by hyperglycaemia[ 45 ] and the interplay between non-alcoholic fatty pancreas development in the milieu of obesity and diabetes[ 46 ].…”
Section: Mechanism Of Development Of Pc In Long-standing T2dmmentioning
confidence: 99%
“…Thus, imidazole propionate level is high in T2D patients [ 84 , 85 ]. Insulin resistance leads to a potential to promote cancer growth: impacts include causing hyperinsulinema, hyperglycemia, and mTOR activation [ 86 , 87 ]. Indeed, imidazole propionate can activate mTOR [ 83 ].…”
Section: Cancer‐promoting Bacteriamentioning
confidence: 99%
“…Indeed, imidazole propionate can activate mTOR [ 83 ]. Insulin resistance results in metabolic alterations, which are important in supporting the uncontrolled growth of tumor cells [ 86 , 88 , 89 ]. Therefore, it is conceivable that impacts of gut microbiota dysbiosis on causing insulin resistance might be involved in promoting cancer growth.…”
Section: Cancer‐promoting Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the specific mechanism of the interaction between diabetes and PC is not fully understood, which is not conducive to the development of strategies for early detection of PC in people with diabetes. Velazquez et al expect to use transcriptome and metabolome changes to reveal the mechanism of diabetes that promotes PC growth and invasion (34). They found that type 2 diabetes mellitus accelerates cancer growth by driving metabolic reprogramming (mainly kynurenine, tryptophan, taurine, and choline pathways), whereas metformin therapy reverses metabolic reprogramming to inhibit cancer growth.…”
Section: Risk Factormentioning
confidence: 99%